Recursos de comunicação online: um estudo sobre percepções discentes acerca de escolhas e prioridades da composição do material didático em ambientes virtuais de aprendizagem - Pereira, Jasete Maria da Silva (2020)
Education, inserted in the context of cyberculture, requires associating human and technological capacity to create communicative resources that aggregate diverse texts, such as images, audio and videos. In this perspective, this thesis based on the theoretical axes that supported it, mentioned in the opening of each section, paid attention to student impressions related to online education, in order to analyze their opinions on the choice of priorities for the content and communication interfaces in environments virtual learning / VLE. Based on an investigative basis supported by qualitative research, the main interest of this study was focused on the following problem: in the student perspective, for online education / eLearning, in the composition of the didactic material, which communication resources need to be prioritized in VLE, aiming at better feedback from students. content among subjects integrated into the teaching-learning process? From the instigation, the central objective that permeated the methodological procedure developed in two Brazilian IPES in the Northeast Region of Brazil, and one IPES in Portugal was to identify with the students of online and semi-distance courses, which communication resources should be privileged, in the composition didactic material in AVA. Thus, to prove if the participants could indicate the communication resources to be privileged in AVA, we developed the research in the period from August / 2016 to October / 2017 in Brazilian territory, and from March to September 2018 in Portugal using the principles of the approach methodological Design-Based Research / DBR. To this end, we rely on the questionnaire, interview and online focus group research instruments, and the contribution of one hundred and six (106) subjects. For the analysis, interpretation and treatment of the data we used content analysis, making it possible to create two categories to structure the didactic material in online education / eLearning: essential and complementary. To answer the question of the thesis more accurately, the evidence showed that, for essential resources, in the first level of classification, students prefer video, followed in descending order by clear statements, Prezi presentation, Power point, virtual objects and gamification. As important as the first category we have as a result for complementary resources books, handouts and study guide since they are dependent and interdependent with each other. In addition, the research subjects emphasized that the teacher's voice media is a communicative interface that must permeate the two classifications, since they directly infer the construction of the student's sense. Thus, from the participants' perceptions, the culmination of this study is represented in the didactic cartography exposed in the last section. I note at the end that student contributions were essential for the thesis, given that they signaled priorities related to the communication resources that make up the teaching material in AVA.